Pengaruh Modal Minimum, Kepatuhan Syariah dan Preferensi Resiko Terhadap Minat Berinvestasi Pasar Modal Syariah - Helma Zuen Anggryani; Miftakhus Surur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of minimum capital, sharia compliance, and risk preferences on interest in investing in the sharia capital market with an understanding of investment as a moderating variable. The case study in this research is generation Z in Bogor. This research uses the SEM PLS method using SmartPLS 4 software. The number of samples in this research was 115 respondents. The research results show that minimum capital does not have a significant effect on investment interest. Sharia compliance has a significant effect on investment interest and risk preferences also have a significant effect on investment interest. Meanwhile, investment understanding cannot yet be a moderating variable on minimum capital. However, investment knowledge is successful and significant as a moderator of the relationship between Sharia Compliance on investment interest and risk preferences on investment interest.